Pericardial Cyst: Never Too Late to Diagnose - Lennon Collins, Katrina (J Clin Med, 2018)
Pericardial cysts are uncommon benign lesions of the middle mediastinum, making up less than 6% of all mediastinal masses. They are often detected as incidental findings on chest imaging and some can resolve spontaneously. Rarely, however, they may cause symptoms of chest pain, right ventricular outflow obstruction, and persistent cough. Furthermore, they may affect cardiac tamponade after acute rupture or cyst haemorrhage resulting in sudden death. We report the case of a 102-year-old woman presenting with urosepsis, in whom routine chest radiography was initially suspicious of advanced bronchial carcinoma. Further imaging supported a diagnosis of one of the largest pericardial cysts described in the literature located in the right parahilar space. The patient was appropriately managed conservatively.